Does the diagnostic timing of cancer-associated thromboembolism influence the survival outcome in ovarian cancer patients? - Jung Chen; Yen-Ling Lai; Jen-Kuang Lee; Han-Wei Lin; Wei-Zen Sun; Yu-Li Chen; Wen-Fang Cheng (Journal of the Formosan Medical Association, 2024)
Background/Purpose: Efforts were made to explore the influence of diagnostic timing for cancer-associated thromboembolic events on survival of ovarian cancer patients. Methods: We reviewed the medical records of 75 ovarian cancer patients with thromboembolism and evaluated the prognostic factors affecting disease-free survival and overall survival. Results: These 75 patients were classified into two categories by the diagnostic timing of the thromboembolism, during (33 cases) and after (42 cases) initial diagnosis of ovarian cancer groups. The diagnostic timing of thromboembolism was not related to disease-free survival or overall survival of the studied population. Advanced disease stage, clear cell histology, interval debulking surgery, no recurrence/persistence of ovarian cancer, and patients treated with anticoagulant(s) treatment >3 months were associated with the disease-free survival. Advanced disease stage, clear cell histology, body mass index (BMI) ≥24 kg/m2 at the diagnosis of ovarian cancer, and no recurrence/persistence of ovarian cancer influenced the overall survival. In the subgroup analysis, compared to the after initial ovarian cancer diagnosis group, patients with stage I/II disease, BMI <24 kg/m2 at the diagnosis of ovarian cancer, or primary debulking surgery in the during cancer diagnosis group had longer disease-free survival, and overall survival benefit was observed in cases with stage I/II disease, or primary debulking surgery. Conclusion: The diagnostic timing of thromboembolism was not related to disease-free or overall survival of ovarian cancer patients, but associated with that of specific patient subgroups.